Spatio-temporal dynamics of root water uptake and identification of soil moisture thresholds for precision irrigation in a Mediterranean yellow-fleshed kiwifruit orchard - Calabritto, Maria; Mininni, Alba N.; Di Biase, Roberto; Pietrafesa, Angela; Dichio, Bartolomeo (Frontiers in Plant Science, 2024)
Actinidia is highly susceptible to water stress, both excess and shortage, and is therefore a model fruit crop for irrigation management, requiring precise water application. The present study was carried out in a mature kiwifruit orchard in southern Italy to investigate the physiology of a yellow-fleshed kiwifruit cultivar under non-limiting soil water conditions and in response to a progressive decrease in soil water content in a Mediterranean environment, with the aim of defining soil moisture thresholds to guide irrigation management. The progressive lowering in soil moisture was monitored using multiprofile probes at different depths, taking into account a 60 cm layer. Plant water status and physiological parameters were measured throughout the experiment and were significantly correlated with soil water status, suggesting that the level of soil water deficit affects plant physiological performance. Reference minimum values of stem water potential reached during the day under nonlimiting soil water conditions ranged from -0.4 to -0.7 MPa, with a value of -0.8 MPa identifying the threshold below which stomatal conductance began to decrease significantly. Soil moisture thresholds were defined according to the spatio-temporal dynamics of available water (AW) reduction, which decreased by approx. 10% and 1% before the onset of water stress and 16% and 2% at the onset of water stress, considered in the 0-30 cm and 30-60 cm soil layers, respectively, compared to the AW content of the whole soil profile. Results confirmed that root uptake was mainly concentrated in the first 30 cm of soil depth, which should be properly managed by irrigation, as reduced soil water availability could easily lead to plant water stress. An integrated approach, combining plant measurements and soil water content monitoring, together with an assessment of root water uptake dynamics, is essential to identify soil water thresholds and develop precision irrigation, especially for high water-demanding crops and environments.